Investigation on evaporation and suppression of SnS during fabrication of Cu2SnS3 thin films. Issue 10 (7th July 2015) - Tang, Zeguo; Kosaka, Kiichi; Uegaki, Hikaru; Chantana, Jakapan; Nukui, Yuki; Hironiwa, Daisuke; Minemoto, Takashi
<x xml:space="preserve">Abstract</x> Reaction processes for fabrication of Cu2SnS3 (CTS) thin films by sulfurization of Cu–Sn precursors are investigated by X‐ray diffraction (XRD) patterns and scanning electron microscope (SEM) images. The results reveal that the S atoms first react with Cu and Sn atoms to produce Cu2–xS, SnS2 and SnS intermediate phases, and it is noted that the bilayer features, i.e., Cu2–xS is located near the surface while SnS and SnS2 are situated at the bottom, are observed initially with the temperature lower than 400 °C. As the temperature increases, these intermediate phases react with each other to form the final CTS phase. Simultaneously, the evaporation of SnS is accompanied by the reaction and consequent voids are formed in the resulting films. In addition, the evaporation of SnS can be suppressed by performing the sulfurization in a sealed space, which is attributed to the increase of partial pressure of SnS and S. A conversion efficiency of 1.2% for a solar cell with structure of Al/ZnO:Al/ZnO/CdS/CTS/Mo/soda lime glass is demonstrated.